PENERAPAN METODE MAUT PEMILIHAN CALON GURU OLAHRAGA DI SDN 101883 PASAR XIII DENGAN PEMBOBOTAN ROC - Siregar, Anggi Yakup; Fadlina, Fadlina; Siregar, Saidi Ramadan (Dharmas Education Journal (DE_Journal), 2024)
The issue at SDN 101883 Pasar XIII is that the selection of physical education teacher candidates relies on the opinions of the school leadership based on pre-established criteria. This practice is reflected in the performance of previous physical education teachers, who were less attentive to students. The objectives of this thesis are to facilitate the process of selecting physical education teacher candidates, enhance the innovative and creative aspects of this process, and to develop the MAUT (Multi Attribute Utility Theory) method and ROC weighting to address issues in the decision support system for selecting physical education teachers. This aims to create a system that is not only efficient and effective but also innovative in its approach, utilizing methods and techniques that can improve overall decision-making. The proposed solution is to use the MAUT method with ROC weighting in the Decision Support System, by identifying the highest to lowest rating values. The research results for determining physical education teacher candidates at SDN 101883 Pasar XIII identified alternative A1, Budi Harahap S.Pd.Kor, with a value of 1.533, as the winning candidate for the position.